Literature Review : Implementasi Peran Konseling Kepolisian dalam Pembinaan Anggota Kepolisian - Sri Utami; Dewi Sulastri; Fathonah Fitri Utami; Syindi Jumaliza; Muhammad Farhan Afandes; Affan Yusra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
One of the programs in the police development process that can be done by counselors is to provide counseling services. This article study aims to find out how the role of counseling is in fostering members of the police force and to find out how the influence of police counseling on members of the police force. By using a literature review or "literature review" with the data collection technique used is a documentation study in the form of a literature study of 20 theoretical studies sourced from reputable articles and books, with 10 strong sources that are relevant to the research conducted by having keywords that are the subject material discussion in the form of the keywords "Counseling" and "Police". Obtaining the results that counseling in the police has a very important role for coaching in solving problems for police officers. Counseling in the police is a preliminary action with the aim of supporting the investigation process with the aim of providing information and awareness about the mistakes and legal responsibilities that the suspect must undergo.